2010
DOI: 10.1002/cctc.201000098
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Microstructure of Li/MgO Catalysts for the Oxidative Coupling of Methane

Abstract: A series of catalysts for the oxidative coupling of methane (OCM) based on MgO with a varying content of Li have been synthesized by the gel‐combustion method. The resulting catalytically active systems are studied by a combination of TEM and SEM methods. Samples with a low abundance of Li exhibit a hierarchical pore system built from tubular structures made from primary MgO particles. Upon calcination at 1073 K, these particles undergo a change in shape from cubic via truncated octahedral to platelet morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 58 publications
3
53
0
6
Order By: Relevance
“…When 745 the ratio was 1, the ethylene selectivity was 30% but increased to 746 40% when the ratio was raised to 4. The trend was generally 747 consistent with observations from studies conducted with related 748 and other OMC catalysts [95,[120][121][122][123][124][125][126][127]. Although natural gas is the main feedstock being considered 783 currently, the re-ignited discovery and production of shale gas 784 could shift the trend toward its valorization via the process.…”
supporting
confidence: 87%
“…When 745 the ratio was 1, the ethylene selectivity was 30% but increased to 746 40% when the ratio was raised to 4. The trend was generally 747 consistent with observations from studies conducted with related 748 and other OMC catalysts [95,[120][121][122][123][124][125][126][127]. Although natural gas is the main feedstock being considered 783 currently, the re-ignited discovery and production of shale gas 784 could shift the trend toward its valorization via the process.…”
supporting
confidence: 87%
“…[6] In return it was shown that lithium, which completely desorbs by formation of volatile compounds during the oxidative pretreatment of the catalyst (which involves the loss of all [Li-O] -centers), acts as a structural promoter that favors the formation of terminating higher index planes like {111} or {110}. [2,7] The highest selectivity to C 2+ products was found for pure MgO catalysts, which expose a greater fraction of {111} planes. [8] Inconsistent findings have also been reported with respect to activity.…”
Section: Li-doped Mgo Was Discovered By Lunsford Et Al As An Active mentioning
confidence: 99%
“…Magnesium oxide (MgO) is an important functional metal oxide that has been widely used in various fields such as catalysis, refractory materials, paints, and superconductors [3,4]. Nanostructured MgO has high surface area and therefore acts as coating agent which helps in increasing the energy conversion efficiency [5].…”
Section: Introductionmentioning
confidence: 99%